In-Depth Thermal Analysis of Different Pin Configurations in Friction Stir Spot Welding of Similar and Dissimilar Alloys - Sajad N. Alasdi; Raheem Al-Sabur (Journal of Manufacturing and Materials Processing)
Over the past decade, friction stir spot welding (FSSW) has gained increasing attention, making it a competitor to conventional welding methods such as resistance welding, rivets, and screws. This type of welding is environmentally friendly because it does not require welding tools and is solid-state welding. This study attempts to demonstrate the importance of pin geometry on temperature distribution and joint quality by using threaded and non-threaded pins for similar and dissimilar alloys. To this end, thermal analysis of the welded joints was conducted using real-time monitoring from a thermal camera and an infrared thermometer, in addition to finite element method (FEM) simulations. The thermal analysis showed that the generated temperatures were higher in dissimilar alloys (Al-Cu) than in similar ones (Al-Al), reaching about 350 °C. In addition, dissimilar alloys show more pronounced FSSW stages through extended periods for each plunging, dwelling, and drawing-out time. The FEM simulation results are consistent with those obtained from thermal imaging cameras and infrared thermometers. The dwelling time was influential, as the higher it was, the more heat was generated, which could be close to the melting point, especially in aluminum alloys. This study provides an in-depth experimental and numerical investigation of temperature distribution throughout the welding cycle, utilizing different pin geometries for both similar and dissimilar non-ferrous alloy joints, offering valuable insights for advanced industrial welding applications.